Synergistic immune protection of exosomal T-cell epitope vaccine and antibody-inducing vaccine against SARS-CoV-2 in highly humanized mice - Shen, Anran; Zhu, Suyue; Li, Min; Zhao, Yu; Wu, Yandan; Zhang, Yue; Zhang, Jiejie; Han, Xuelian; Wang, Yuan; Zhao, Guangyu; Lv, Linli; Yin, Qi; et al. (Frontiers in Immunology, 2026)
ObjectiveTo evaluate the synergistic immunological protection of exosomal T-cell epitope vaccine and antibody-inducing vaccine against SARS-CoV-2 in highly humanized mice.MethodsRed blood cell-derived exosomes were loaded with 27 CD8+ T-cell epitope peptides and 19 CD4+ T-cell epitope peptides followed by combined immunization with S1 protein vaccine of SARS-CoV-2 and adjuvant poly I:C in HLA-A2/DR1 double transgenic mice. After immunizations, splenocytes were assessed for epitope-specific T cell responses by intracellular cytokine staining and ELISPOT, and for functional T cell subset analysis through flow cytometry. Meanwhile, serum anti-S1 protein IgG and neutralizing antibodies were quantified via ELISA and BA.5 pseudovirus neutralization assay, respectively. Furthermore, viral challenge was performed after the combined immunization in HLA-A2/DR1/hACE2 triple transgenic mice, followed by viral load quantification, viral protein detection, and H&E staining in lungs.ResultsThe combined immunization i) increased the titers of S1 protein-specific IgG antibodies and neutralizing antibodies as well as Tfh cell frequency as compared to the S1 protein vaccine alone; ii) induced significantly more S1 protein-specific T cells and effector memory CD4+ T cells, and inhibited T cell exhaustion and regulatory T cell differentiation, compared to the exosomal T-cell epitope vaccine alone; iii) achieved the lowest pulmonary viral loads, inflammatory cell infiltration, and histopathological damage after SARS-CoV-2 infection.ConclusionThis study, for the first time, demonstrates the synergistic humoral and cellular immune responses and protective efficacy induced by the combined immunization of exosomal T-cell epitope vaccine and antibody-inducing vaccine, and provides preclinical evidence from highly humanized mice for optimizing next-generation SARS-CoV-2 vaccine protocols.